A study on the enhancement of the reliability in gravure offset roll printing with blanket swelling control. (9th September 2016) - Kim, Ga Eul; Woo, Kyoohee; Kang, Dongwoo; Jang, Yunseok; Choi, Young-Man; Lee, Moon G; Lee, Taik-Min; Kwon, Sin
Abstract: In roll-offset printing (patterning) technology with a PDMS blanket as a transfer medium, one of the major reliability issues is the occurrence of swelling, which involves absorption of the ink solvent in the printing blanket with repeated printing. This study developed a method to resolve blanket swelling in gravure offset roll printing and performed experiments for performance verification. The physical phenomena of mass and heat transfer were applied to fabricate a device based on convection drying. The proposed device managed to effectively control blanket swelling through drying by blowing air and additional temperature control. The experiments verified that printing quality (in particular the variation of the width of printed patterns) was maintained over 500 continuous printing.